Leukocyte Count and Intracerebral Hemorrhage Expansion - Morotti, Andrea (Stroke, 2016)
BACKGROUND AND PURPOSE: Acute leukocytosis is a well-established response to intracerebral hemorrhage (ICH). Leukocytes, because of their interaction with platelets and coagulation factors, may in turn play a role in hemostasis. We investigated whether admission leukocytosis was associated with reduced bleeding following acute ICH. METHODS: Consecutive patients with primary ICH were prospectively collected from 1994 to 2015 and retrospectively analyzed. We included subjects with a follow-up CT scan available and automated complete white blood cell (WBC) count performed within 48 h from onset. Baseline and follow-up hematoma volumes were calculated with semi-automated software and hematoma expansion was defined as volume increase > 30% or 6 mL. The association between WBC count and ICH expansion was investigated with multivariate logistic regression. RESULTS: 1302 subjects met eligibility criteria (median age 75 years, 55.8 % males), of whom 207 (15.9 %) experienced hematoma expansion. Higher leukocyte count on admission was associated with reduced risk of hematoma expansion (Odds Ratio for 1000 cells increase [OR] 0.91, 95 % Confidence Interval [CI] 0.86–0.96, p=0.001). The risk of hematoma expansion was inversely associated with neutrophil count (OR 0.90, 95 % CI 0.85–0.96, p=0.001) and directly associated with monocyte count (OR 2.71, 95 % CI 1.08–6.83, p=0.034). There was no association between lymphocyte count and ICH expansion (OR 0.96, 95 % CI 0.79–1.17, p=0.718). CONCLUSIONS: Higher admission WBC count is associated with lower risk of hematoma expansion. This highlights a potential role of the inflammatory response in modulating the coagulation cascade following acute ICH.